Exploring Strategic Change - Balogun Julia; Hailey Veronica Hope (Prentice Hall Europe, 1999)
This book expands on the strategic change issues covered in Exploring Corporate strategy. Exploring Strategic change: an introduction, Understanding implementation choices: the options to consider, Analyzing the change context: the change kaleidoscope, Analyzing the change context: making change judgements, Designing the transition: the implementation path, Designing the transition: levers and mechanisms, Managing the transition: resourcing and monitoring, Concluding comments, Appendices.